2022
DOI: 10.15252/msb.202211186
|View full text |Cite
|
Sign up to set email alerts
|

Systematic multi‐level analysis of an organelle proteome reveals new peroxisomal functions

Abstract: Seventy years following the discovery of peroxisomes, their complete proteome, the peroxi-ome, remains undefined. Uncovering the peroxiome is crucial for understanding peroxisomal activities and cellular metabolism. We used high-content microscopy to uncover peroxisomal proteins in the model eukaryote -Saccharomyces cerevisiae. This strategy enabled us to expand the known peroxi-ome by ~40% and paved the way for performing systematic, whole-organellar proteome assays. By characterizing the sub-organellar local… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 102 publications
1
17
0
1
Order By: Relevance
“…Indeed, most IMS proteins contain a conserved pattern of cysteine residues present in the “twin CX 3 C or CX 9 C motifs” (Vögtle et al, 2012) with a direct impact on the regulation of redox-sensitive cellular processes between the mitochondria and other compartments of the cell (Nuebel et al, 2016). Similarly to Dmo2p, many IMS products present dual localization (Yifrach et al, 2022); in this study, we corroborate these previous observations about Dmo2p localization.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…Indeed, most IMS proteins contain a conserved pattern of cysteine residues present in the “twin CX 3 C or CX 9 C motifs” (Vögtle et al, 2012) with a direct impact on the regulation of redox-sensitive cellular processes between the mitochondria and other compartments of the cell (Nuebel et al, 2016). Similarly to Dmo2p, many IMS products present dual localization (Yifrach et al, 2022); in this study, we corroborate these previous observations about Dmo2p localization.…”
Section: Introductionsupporting
confidence: 92%
“…Oleate is an oxidative medium known to induce peroxisome biogenesis and activity (Venhuis et al, 1987). This experiment was motivated by previous findings that suggested the presence of Dmo2p associated with peroxisome membranes or membrane periphery (Yifrach et al, 2022). In yeast, peroxisomes carry out the β-oxidation of fatty acids to generate acetyl-CoA, which produces high levels of reactive oxygen species (ROS) as byproducts; indeed, mitochondria and peroxisome play central roles in the metabolism of ROS, with a common evolutionary origin (Bolte et al, 2015), they also share components of the fusion-fission machinery (Fransen et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Horizontal and vertical lines indicate a p-value of 0.05 and a fold-change of ≤ 0.66 or ≥ 1.5, respectively. Information about a peroxisomal localization of proteins or association with peroxisomes is based on (David et al, 2022; Elbaz-Alon et al, 2014; Marelli et al, 2004; Motley et al, 2012; Tanaka et al, 2014; Yifrach et al, 2022). PO, peroxisomal and peroxisome-associated proteins or transcripts.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies on S. cerevisiae peroxisomes (Yifrach et al, 2022) and mitochondria (Morgenstern et al, 2017) showed that the proteomes of both organelles contain numerous multi-localized proteins. Thus, we hypothesized that solute transporters of other cellular compartments might partially localize to peroxisomes.…”
Section: Mpc1 and Mpc3 Are So Far Unknown Transporters Of The Peroxis...mentioning
confidence: 99%
See 1 more Smart Citation